Local vibrational density of states in disordered graphene - Kardashev, D.L.; Kardashev, K.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Local vibrational density of states for disordered graphene has been calculated via Green’s functions method. Disordered material has been modeled with Bethe lattice. Density of states does not include particularities specific for ideal graphene.